2020
DOI: 10.34172/jnp.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between microalbuminuria, overweight and obesity

Abstract: Introduction: Diabetes, hypertension and obesity are associated with endothelial dysfunction. The first sign of endothelial dysfunction is microalbuminuria. Objectives: The aim of this study was to measure urine albumin to creatinine ratio in obese patients without diabetes and with normal blood pressure. Patients and Methods: In this cross-sectional study, 200 adults were chosen with body mass index (BMI) ≥25 kg/m2 . Anthropometry measurements [BMI and waist to hip ratio (WHR)] and biochemical tests were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Concerning the relationship between gender and microalbuminuria levels, this study showed a significant difference among obese and normal-weight girls but not among boys. In contrast, Hemayati et al (26) found that the prevalence of microalbuminuria was 11% and was significantly higher in men than women. Rutkowski et al, (27) also found that microalbuminuria was higher in men than women.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Concerning the relationship between gender and microalbuminuria levels, this study showed a significant difference among obese and normal-weight girls but not among boys. In contrast, Hemayati et al (26) found that the prevalence of microalbuminuria was 11% and was significantly higher in men than women. Rutkowski et al, (27) also found that microalbuminuria was higher in men than women.…”
Section: Discussionmentioning
confidence: 86%
“…Rutkowski et al, (27) also found that microalbuminuria was higher in men than women. Obesityrelated glomerulopathy presented clinically by microalbuminuria and may increase tenfold over 15 years (26). The development of increased albumin excretion rates is associated not only with hyperglycemia but also with blood pressure elevations (28).…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) and waist-to-hip ratio (WHR) have been significantly associated with microalbuminuria [10]. The specific pathogenesis regarding obesity-related glomerulopathy is hyperfiltration, which is mediated by excessive protein and salt intake, high blood insulin levels, and increased feedback of the tubuloglomerular component.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] A reduction in central obesity should be emphasized as a key component for the prevention of vascular and renal function decline. [18,19] . The term 'insulin resistance' refers to a decrease in a target cell's metabolic response to insulin, or, at the whole-organism level, an impaired lowering effect of circulating or injected insulin on blood glucose.…”
Section: Introductionmentioning
confidence: 99%